2017
DOI: 10.1016/j.ijdevneu.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of early‐life stress on dopamine system function in adolescent female rats

Abstract: During adolescence, many neural systems, including the dopamine system, undergo essential remodeling and maturation. It is well known that early-life stress (ELS) increases the risk for many psychopathologies during adolescence and adulthood. It is hypothesized that ELS interferes with the maturation of the dopamine system. There is a sex bias in the prevalence of stress-related mental disorders. Information regarding the effects of ELS on brain functioning in females is very limited. In the current study, mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 83 publications
0
23
1
Order By: Relevance
“…In the mesolimbic circuit, particularly within the VTA-NAc projection, ELS causes long-term changes in dopaminergic activity. Both animal and human studies have reported an increase in stressinduced dopamine release during adulthood (Hall et al, 1999;Brake et al, 2004;Pruessner et al, 2004;Yorgason et al, 2013), and animal studies have shown long-lasting changes in dopamine receptors including decreased NAc D2R expression in prenatally stressed rats treated with nicotine (Said et al, 2015) as well as in rats subjected to maternal separation (Majcher-Maślanka et al, 2017). As previously mentioned, decreased density of the D2R in the NAc is thought to be an important contributor to drug craving (Volkow et al, 1993.…”
Section: Early Life Stressmentioning
confidence: 96%
“…In the mesolimbic circuit, particularly within the VTA-NAc projection, ELS causes long-term changes in dopaminergic activity. Both animal and human studies have reported an increase in stressinduced dopamine release during adulthood (Hall et al, 1999;Brake et al, 2004;Pruessner et al, 2004;Yorgason et al, 2013), and animal studies have shown long-lasting changes in dopamine receptors including decreased NAc D2R expression in prenatally stressed rats treated with nicotine (Said et al, 2015) as well as in rats subjected to maternal separation (Majcher-Maślanka et al, 2017). As previously mentioned, decreased density of the D2R in the NAc is thought to be an important contributor to drug craving (Volkow et al, 1993.…”
Section: Early Life Stressmentioning
confidence: 96%
“…Our previous study showed that DRD1 and DRD2 gene expression were increased in the brainstem of adult rats, accompanied by higher palatable food intake after MS (de Souza et al, 2018). The MS also modulates the DA system in other brain areas, such as PLC, NAcc, and striatum, changing the density of immunoreactive fibers of TH, and the mRNA expression of DRD2, DRD1, and DRD5 (Majcher-Maślanka et al, 2017). On the other hand, EW increases DRD1 mRNA expression in the hypothalamus and brainstem and DRD2 in the brainstem of middle-aged male rats (Tavares et al, 2020b).…”
Section: Dopamine: Role On Feeding Behavior Influences Of Els and Mmentioning
confidence: 99%
“…Numerous studies have investigated the effects of early-life stress, but only in the past decade have females been included in the research cohorts (Barbosa Neto et al, 2012;Dalaveri, Nakhaee, Esmaeilpour, Mahani, & Sheibani, 2017;Dimatelis, Vermeulen, Bugarith, Stein, & Russell, 2016;Loi et al, 2015;Lukkes, Meda, Thompson, Freund, & Andersen, 2017;Majcher-maslanka, Solarz, Krzysztof, & Chocyk, 2017;Sun, Tu, Shi, Xue, & Zhao, 2014;Xiong, Yang, Wang, Xu, & Mao, 2014). In a previous study in our laboratory, we demonstrated how MS affects male rats' spatial memory (Banqueri, Méndez, & Arias, 2017), In the present study, we want to further explore spatial memory, in this case with females, while also testing cognitive flexibility.…”
Section: Introductionmentioning
confidence: 99%